Development and content validity of new patient-reported outcome questionnaires to assess the signs and symptoms and impact of atopic dermatitis: the Atopic Dermatitis Symptom Scale (ADerm-SS) and the Atopic Dermatitis Impact Scale (ADerm-IS). (3rd July 2019) - Foley, Catherine; Tundia, Namita; Simpson, Eric; Teixeira, Henrique D.; Litcher-Kelly, Leighann; Bodhani, Amit
Abstract: Objectives: Atopic dermatitis (AD) is a chronic, relapsing skin condition, with signs and symptoms that impact patients' lives and are best measured from the patient perspective. Therefore, there is a need for AD-specific questionnaires that are consistent with Food and Drug Administration guidance and best measurement practices, assessing sign and symptom severity and associated impacts, to support treatment efficacy in regulated trials. The objectives were to develop patient-reported outcome (PRO) questionnaires assessing sign and symptom severity, as well as impacts of moderate-to-severe adult AD. Methods: A targeted literature review and meetings with clinical experts (dermatologists) were conducted to identify AD-related sign, symptom, and impact concepts. Results were harmonized and used to construct two draft PRO questionnaires: the Atopic Dermatitis Symptom Scale (ADerm-SS; 11 items) and the Atopic Dermatitis Impact Scale (ADerm-IS; 10 items). The content validity and questionnaire content were evaluated via qualitative concept elicitation/cognitive debriefing interviews with adult patients with moderate-to-severe AD. Results: From the literature ( n  = 13 articles), 13 sign and symptom and 43 impact concepts were identified, while 21 sign and symptom and 48 impacts were elicited from experts ( n  = 3). During the patient interviews ( n  = 15), 19 sign and symptom and 41 impact concepts were reported, the majority of which were evaluated by the ADerm-SS and ADerm-IS, thus substantiating the content of both questionnaires. Additionally, patients interpreted both questionnaires as intended by the developers. Conclusions: The ADerm-SS and ADerm-IS can be regarded as content-valid PRO questionnaires for moderate-to-severe AD.